Towards University Innovation Belt: Problems of Management - R. G. Strongin; E. V. Chuprunov (Moscow Polytechnic University, 2018)
The article is a continuation of the series [1-4] devoted to the analysis of Nizhniy Novgorod Lobachevski University multidisciplinary cluster development, which aims at supporting forward education in the area of biomedicine and biotechnologies. This analysis serves as a basis for deriving some new approaches to manage the cluster evolution. Main emphasis is focused on the need of integration with multiple partners to attract the material and human resources for implementing the project. This integration results in interosculation of administrative (transformation of university structure) and project (networking) approaches to university management. Putting intooperation of a new building (25 thousand sq. m.) for the University center of innovative development provides facilities for spatial merger of the increasing number of administrative and network cluster nodes. This is an important step in the development of university innovation belt which characterizes the third generation university. The approaches to govern the whole cluster are under consideration.